Creating a Drosophila wing de novo, the role of engrailed, and the compartment border hypothesis. - Tabata, T.; Schwartz, C.; Gustavson, E.; Ali, Z.; Kornberg, T.B. (Development, 1995)
Anterior/posterior compartment borders bisect every Drosophila imaginal disc, and the engrailed gene is essential for their function. We analyzed the role of the engrailed and invected genes in wing discs by eliminating or increasing their activity. Removing engrailed/invected from posterior wing cells created two new compartments: an anterior compartment consisting of mutant cells and a posterior compartment that grew from neighboring cells. In some cases, these compartments formed a complete new wing. Increasing engrailed activity also affected patterning. These findings demonstrate that engrailed both directs the posterior compartment pathway and creates the compartment border. These findings also establish the compartment border as the pre-eminent organizational feature of disc growth and patterning.